Manipulation in the in situ growth design parameters of aqueous zinc-based electrodes for batteries: The fundamentals and perspectives - Nurul Akmal, Che Lah (Wiley, 2024)
Precise exploitation of the growth of Zn metal anode in a power converter system has re-emerged as one of the technological interests that have surged globally in the past 5 years, specifically to improve the practical use of deep cycling metal batteries. In this review, the in situ architectures of aqueous Zn metal-based batteries focusing on the intrinsic geometrical building block and their respective mode of assembly classifying the deposition morphologies are scrutinised and discussed. The fundamental electrochemical kinetic principles and the associated critical issues, especially associated with the metal plague deposition that influences the morphology of deposited Zn, are considered. Also, the growing interest in the interphase system, which has an intense influence in characterising the types of Zn deposition morphology, is included. Consideration of the fundamental crystal features of Zn, endowing the predominant key for its growth assembly, is provided. Last, the review offers perspectives on the current progress of Zn–Air batteries in the application of electric vehicles.